Impactos do consumo de álcool, tabagismo e sedentarismo sobre as tábuas de mortalidade - Zalcberg, Henrique Girotto (2023)
This study explores the relationship between lifestyle habits, life expectancy, and their impact on actuarial tables and life insurance companies. The objective is to analyze how sedentary behavior, smoking, and excessive alcohol consumption affect people's longevity and influence insurance pricing practices. The research aims to contribute to more accurate underwriting strategies, preparing insurance companies for emerging challenges related to modern lifestyles. The justification lies in the need to understand how these detrimental habits impact not only individuals' health but also the financial sustainability of insurance companies, enabling the adaptation of policies that reflect the realities of contemporary lifestyles